A critical evaluation of the involvement of pastors with mental patients : a case study of Saint John of God Mental Hospital in Mzuzu, Malawi - Kamanga, Chrispine Nthezemu (Stellenbosch : Stellenbosch University, 2019)
Thesis (MTh)--Stellenbosch University, 2019.